Contribution of multimodal ultrasound in evaluating the efficacy of lumbricus protein fast dissolving tablets against atherosclerotic plaques in ApoE(−/−) mice - Lu, Zhihao; Wang, Ning; Yu, Quanlin; Feng, Jing; Dong, Jianteng; Zhao, Xu; Cai, Chengke; Li, Jian; Zhong, Liqun (Frontiers in Pharmacology, 2025)
IntroductionAtherosclerosis (AS), a prevalent cardiovascular condition characterized by cholesterol accumulation, inflammation, and fibrous tissue proliferation within arterial walls, remains a major global health challenge. Traditional Chinese Medicine (TCM) identifies earthworm (Lumbricus) as an effective treatment for blood stasis syndromes. Some studies have identified lumbricus-derived extracts as being rich in collagenase and fibrinolytic enzymes, which has significant effects in dissolving blood clots, improving circulation, and preventing thrombosis. Therefore, in the present study, a novel formulation, fast dissolving tablets of lumbricus protein (abbreviated as: LP-FDT), was developed as part of upcoming new drug research and development, and we used multi-modal ultrasonic technique combined with routine biochemical and histopathological analysis methods to evaluate its efficacy on AS. By leveraging the advantages of LP-FDT and adhering to the principle of the 3Rs (replacement, reduction, refinement), this research offers a novel and sustainable therapeutic strategy for managing AS. The findings from this study are expected to provide valuable insights into the development of patient-friendly treatments for AS, bridging the gap between traditional therapies and modern pharmaceutical innovations.MethodsAnimal model was established by ApoE-/- feeding high-fat diet for 8 weeks. Multimodal ultrasound, along with histopathological and biochemical analyses, was employed to assess the therapeutic effects.ResultsLP-FDT significantly reduced arterial plaque size and inflammation while enhancing collagen remodeling within the plaques. Although no substantial impact on serum lipid profiles was observed, LP-FDT significantly downregulated MMP-2 and MMP-9 expression, suggesting a novel immunomodulatory mechanism in extracellular matrix degradation and plaque stabilization.DiscussionIn this study, we confirmed the efficacy of LP-FDT for AS by multimodal ultrasound, along with histopathological and biochemical analyses. At the same time, by adhering to the principles of the 3Rs (replacement, reduction, refinement), the study minimized animal use and suffering while maximizing experimental reliability. The findings of this study indicate that LP-FDT, an innovative formulation combining TCM principles with modern pharmaceutical technologies, holds significant promise in the prevention and treatment of AS, providing a new pathway for the integration of traditional and contemporary approaches to cardiovascular health. Further investigation into its molecular mechanisms is warranted.